Epigenetic modulation of the NLRP6 inflammasome sensor as a therapeutic modality to reduce necroptosis-driven gastrointestinal mucosal dysfunction in HIV/SIV infection - Lakmini S. Premadasa; Marina McDew-White; Luis Romero; Beverly Gondo; Jade A. Drawec; Binhua Ling; Chioma M. Okeoma; Mahesh Mohan (Cell Communication and Signaling)
Abstract Background Gastrointestinal (GI) disease/dysfunction persists in people living with HIV (PLWH) receiving suppressive combination anti-retroviral therapy (ART) leading to epithelial barrier breakdown, microbial translocation and systemic inflammation that can drive non-AIDS associated comorbidities. Although epigenetic mechanisms are predicted to drive GI dysfunction, they remain unknown and unaddressed in HIV/SIV infection. The present study investigated genome-wide changes in DNA methylation, and gene expression exclusively in colon epithelial cells (CE) in response to simian immunodeficiency virus infection (SIV) and long-term low-dose delta-9-tetrahydrocannabinol (THC). Methods Using reduced-representation bisulfite sequencing, we characterized DNA methylation changes in colonic epithelium (CE) of uninfected controls (n=5) and SIV-infected rhesus macaques (RMs) administered vehicle (VEH/SIV; n=7) or THC (THC/SIV; n=6). Intact jejunum resection segments (~5cm) were collected from sixteen ART treated SIV-infected RMs [(VEH/SIV/ART; n=8) and (THC/SIV/ART; n=8)] to confirm protein expression data identified in the colon of ART-naïve SIV-infected RMs. Transcriptomics data was used to confirm expression of differentially methylated genes. Protein expression of differentially methylated genes and their downstream targets was assessed using Immunofluorescence followed by HALO quantification. Results SIV infection in ART-naïve RMs induced marked hypomethylation throughout promoter-associated CpG islands (paCGIs) in genes related to inflammatory response (NLRP6, cGAS), cellular adhesion (PCDH17, CDH7) and proliferation (WIF1, SFRP1, TERT, and HAND2) in CEs. Moreover, low-dose THC reduced NLRP6 protein expression in CE by hypermethylating the NLRP6 paCGI and blocked polyI:C induced NLRP6 upregulation in vitro. In ART suppressed SIV-infected RMs, significant NLRP6 protein upregulation during acute infection was unaffected by long-term ART administration during chronic infection despite successful plasma and tissue viral suppression. In this group, NLRP6 protein upregulation was associated with significantly increased expression of necroptosis-driving proteins; phosphorylated-RIPK3(Ser199), phosphorylated-MLKL(Thr357/Ser358), and HMGB1. Most strikingly, adding ART to THC-treated SIV-infected RMs effectively reduced NLRP6 and necroptosis-driving protein expression to pre-infection levels. Conclusions We conclude that DNA hypomethylation-assisted NLRP6 upregulation can lead to its constitutively high expression resulting in the activation of necroptosis signaling via the RIPK3/p-MLKL pathway that can eventually drive intestinal epithelial loss/death. From a clinical standpoint, low-dose phytocannabinoids in combination with ART could safely and successfully reduce/reverse persistent GI inflammatory responses via modulating DNA methylation.